PENGARUH PELATIHAN DAN PEMOTIVASIAN TERHADAP KINERJA KARYAWAN PADA KOPERASI KARYA USAHA MANDIRI SYARIAH CABANG NANGGUNG, KABUPATEN BOGOR - Dedi Yudistira; Miftakhul Anwar; Azizah Mursyidah (SAHID BANKING JOURNAL, 2022)
The objectives of this study include: (1) To analyze the effect of training on employee performance, (2) To analyze the effect of motivation on employee performance, (3) To analyze the effect of training and motivation on employee performance at Karya Usaha Mandiri Nanggung. This study uses quantitative methods with analytical descriptive research, the method of determining the sample using the slovin method, the number of samples used in this study was 51 respondents of employees of the independent branch of Nanggung which were collected through questionnaires. The results of the study at a significant level of 0.05 found: (1) training had a positive and significant effect on employee performance. (2) motivation has a positive and significant effect on employee performance, (3) training and motivation together have a significant effect on employee performance in the work of an independent sharia business in the Nanggung branch.